2013
DOI: 10.1108/rpj-12-2011-0133
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxidation on the cracks of DZ125L nickel-based superalloy thin-walled parts in laser metal direct forming

Abstract: Purpose -The purpose of this paper is to investigate the influence of the oxidation on the cracks of DZ125L nickel-based superalloy thin-walled parts in laser metal direct forming (LMDF). Design/methodology/approach -Thin-walled cylinders were fabricated in protective atmosphere with different oxygen contents in order to reveal the influence of oxidation on the morphology of cracks. The influence of oxidation on the cracks was investigated in detail by measuring the wall thicknesses of cylinders, the residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Irrespective of the type of oxides, compressive stress is established in this thermally-grown oxide because of the diffusion. This leads to plastic deformation inside the oxide and along the interface between the oxide and the matrix in an effort to release the stress, which incurs intergranular voids attributable to the grain boundary sliding [ 45 , 73 ], resulting in the crack initiation and propagation at areas of stress concentration [ 73 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Irrespective of the type of oxides, compressive stress is established in this thermally-grown oxide because of the diffusion. This leads to plastic deformation inside the oxide and along the interface between the oxide and the matrix in an effort to release the stress, which incurs intergranular voids attributable to the grain boundary sliding [ 45 , 73 ], resulting in the crack initiation and propagation at areas of stress concentration [ 73 , 74 , 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was difficult to obtain the stoichiometry of the oxides from the quantitative composition in Table 3 because of the multiple elements detected. The results of the spot analyses on the oxides were unavoidably affected by the X-ray spectra from the matrix under the oxides due to the increased excitation volume caused by high accelerating voltage [ 62 , 63 ], which made it difficult to determine the ideal chemical formula such as Al 2 O 3 and TiO 2 . However, these oxide formations can be explained by thermodynamic data as follows.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, plastic deformation occurs to release the stress within the oxide and along the interface between the oxide and the matrix, which generates intergranular voids due to the grain boundary sliding [ 67 ]. These voids and continuous plastic deformations result in the crack initiation and propagation at the stress concentration area [ 62 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, He et al (2013) and Zhong et al (2005) also reported the occurrence of cracking in manufacturing DZ125L (wt.% (Al+Ti) = 8.0%) and IN738 (wt.% (Al+Ti) = 7.0%) by DLF, respectively. Thus, as for Rene 104 containing about 7.1 wt.% (Al + Ti) as well as 8.3 wt.% refractory elements (Ta, W, Mo), it will even be more sensitive to cracking and defects during DLF than other series of superalloys.…”
Section: Introductionmentioning
confidence: 91%